Penggunaan Model Pembelajaran Visualization, Auditory, Kinestetic untuk Meningkatkan Hasil Belajar Siswa - Karlina, Ina; Aminy, Fadlilah Aisyah (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2016)
This research is motivated by the low learning outcomes of students in science subjects. It is characterized by the fact that most of the daily test scores of students have not reached the minimum standard. The use of models Visualization, Auditory, Kinestetic (VAK) in learning science is proven to improve the quality of learning that is evidenced by the increase in the ability of teachers in implementing the learning cycle I is 77.3% -77.75% and 78.55% -79 in second cycle, 5%. While improving student learning outcomes in learning science increased from the first cycle of 36% -45% to 50% -77% in the second cycle.